Validity of the RAST for evaluating anaerobic power performance as compared to Wingate test in cycling athletes - Queiroga,Marcos Roberto (2013)
The validity of the Running-based Anaerobic Sprint Test (RAST) was investigated to evaluate the anaerobic power performance in comparison to Wingate test in cycling athletes. Ten mountain-bike male cyclists (28.0±7.3 years) randomly performed Wingate Test and RAST with two trials each. After several anthropometric measurements, peak power (PP), mean power (MP) and fatigue index (FI) for RAST and Wingate Test were analyzed using Student's paired t-test, Pearson's linear correlation test (r) and Bland and Altman's plots. Results showed that, with the exception of FI (33.8±4.6% vs. 37.8±7.9%; r=0.172), significant differences were detected between the Wingate and RAST tests with regard to PP and MP. Although there was a strong correlation for PP and MP, or rather, 0.831 and 0.714 respectively, agreement of analysis between Wingate and RAST protocols was low. The above suggested that RAST was not appropriate to evaluate the performance of anaerobic power by Wingate test in cycling athletes.